Loading simulation of lumbar spine vertebrae during a compression test using the finite elements method and trabecular bone strength properties, determined by means of nanoindentations - Bouzakis, K D; Mitsi, S; Michailidis, N; Mirisidis, I; Mesomeris, G; Maliaris, G; Korlos, A; Kapetanos, G; Antonarakos, P; Anagnostidis, K (Journal of musculoskeletal & neuronal interactions, 2004)
The mechanical strength properties of lumbar spine vertebrae are of great importance in a wide range of applications. Herein, through nanoindentations and appropriate evaluation of the corresponding results, trabecular bone struts stress-strain characteristics can be determined. In the frame of the present paper, an L2 fresh cadaveric vertebra, from which posterior elements were removed, was subjected to compression. With the aid of developed finite elements method based algorithms, the cortical shell and the cancellous core bulk elasticity moduli and stresses were determined, whereas the tested vertebra geometrical model used in these algorithms was considered as having a compound structure, consisting of the cancellous bone surrounded by the cortical shell. Moreover nanoindentations were conducted and an appropriate evaluation method of the obtained results was applied to extract stress-strain curves of individual lumbar spine vertebra trabecular bone struts. These data were used in the mathematical description of the vertebrae compression test. The vertebral cancellous bone structure was simulated by a beam elements network, possessing an equivalent porosity and different stiffnesses in vertical and horizontal direction. Thus, the measured course of the compression load versus the occurring specimen deformation was verified.